Farmer boy - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York, Harper, 1953)
Nine-year-old Almanzo lives with his family on a big farm in New York State at the end of the nineteenth century. He raises his own two calves, helps cut ice and shear sheep, and longs for the day he can have his own colt.
Keywords: Wilder, Almanzo -- Juvenile fiction; Wilder, Almanzo -- Fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Family -- Fiction; Farm life -- New York (State) -- Fiction; Families -- New York (State) -- Fiction; New York (State) -- Fiction